2016
DOI: 10.4265/bio.21.187
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Action of Photodynamic Antimicrobial Chemotherapy (PACT) with Photosensitizers Used as Plaque-Disclosing Agents against Experimental Biofilm

Abstract: Our previous study revealed that the photo-irradiation of rose bengal, erythrosine, and phloxine, xanthene photosensitizers, used as dental plaque disclosing agents, could exert bactericidal action on planktonic Streptococcus mutans via the singlet oxygen. In the present study, the photo-irradiation induced bactericidal activity of the three xanthene compounds against the experimental biofilm of S. mutans was investigated in combination with acid electrolyzed water AcEW and alkaline electrolyzed water AlEW . A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As a consequence, it is strongly advocated that RB-AlEW could be applied to treat dental biofilms. Since Ishiyama's study dealt with a single-species S. mutans biofilm, the effect on mixed-species biofilms should be examined in the near future in order to further ascertain the feasibility of the treatment's application in dentistry [41] ( Table 1).…”
Section: Electrolyzed Watermentioning
confidence: 99%
“…As a consequence, it is strongly advocated that RB-AlEW could be applied to treat dental biofilms. Since Ishiyama's study dealt with a single-species S. mutans biofilm, the effect on mixed-species biofilms should be examined in the near future in order to further ascertain the feasibility of the treatment's application in dentistry [41] ( Table 1).…”
Section: Electrolyzed Watermentioning
confidence: 99%
“…In contrast, photo-irradiated rose bengal in AlEW showed prominent bactericidal activity of viable bacterial count, suggesting that PACT with rose bengal in combination with AlEW could be applied to treat dental biofilm. In a previous study Ishiyama K. et al (2012) showed that of the three photo sensitizers tested, rose bengal exerted the highest bactericidal activity against planktonic S. mutans, most likely due to its high incorporation efficiency into bacterial cells [22,23]. 2015) revealed in their study that in patients with aggressive periodontitis (AgP) the use of amoxicillin and metronidazole resulted in a statistically significant reduction of matrix metalloproteinase 8 and 9 MMP-8 gingival crevicular fluid GCF levels at 3 and 6 months after treatment.…”
Section: Porphyrinsmentioning
confidence: 98%
“…Modification of Gram-stain is rarely done, but discoveries for alternatives have been done in several recent researchers by using different dyes or stains, which result in higher contrast [6]. In other cases, novel staining methods were developed in dentistry to detect the presence of oral biofilm in the teeth and gums [10,18]. However, the experiments tend to use pure compounds and do not generally use foodcoloring dyes directly.…”
Section: Issn 2087-2852 E-issn 2338-1655mentioning
confidence: 99%